Esperança e promoção da saúde mental de mães de prematuros internados em Unidade de Terapia Intensiva Neonatal - Albers, Mariana Barbosa Ferreira (Universidade Federal de São Carlos, 2023)
The birth of premature infants can lead to experiences of hospitalization in the Neonatal Intensive Care Unit for mothers and their families, where specialized care is provided but negative experiences are also encountered. This fact can trigger negative impacts on these women, potentially affecting their mental health. In this context, hope has been recognized and considered as a resource for care, contributing to adaptation and resilience. The general objective of this study was to analyze the perceptions and experiences of hope among mothers of premature newborns hospitalized in Neonatal Intensive Care Units (NICUs) and its repercussions on their mental health during the COVID-19 pandemic. The specific objective was to analyze the perception of mothers of premature infants hospitalized in NICUs regarding inhibiting and promoting factors of hope during the pandemic context. The study employed a qualitative approach, conducting face-to-face semi-structured interviews with twelve mothers of premature infants hospitalized in a Neonatal Intensive Care Unit in a city of a State of São Paulo , where the mother is not allowed to stay in the unit and visiting hours are restricted. During the research period, which took place during the pandemic, visits were limited to the parents of the premature infants. Thematic reflective analysis was the adopted method, anchored in the theoretical construct of Dufault and Martocchio's Model of Hope. The study was analyzed and approved by the Research Ethics Committee for Human Beings of a Federal University in a city of São Paulo State, with opinion number 5,129,909 in the year 2021. The results emphasized that the process of hope is based on life circumstances that generate learning in a context that promotes coexistence with ambivalent feelings. Hope presented various conceptual meanings for these mothers; however, it constituted a process that is oriented towards the future while holding expectations of something possible, even in the face of uncertainties. In this context, women recognized situations/factors that promoted or inhibited hope. Sources of hope were represented by people in the family circle, healthcare professionals, religious beliefs, and improvement in the neonate's clinical condition. Inhibiting factors for hope were related to the mother's perception of the fragility of the neonate, including deterioration in the premature infant's clinical condition, physical suffering, as well as concerns about future impairments and damages to the physical and mental development of the premature newborn. It can be concluded that in recognizing healthcare and nursing teams as sources of hope, these professionals require relational and intrapersonal competence and skills to assist patients in the process of identifying factors and sources that promote or inhibit hope. Therefore, to achieve this objective, it is necessary to incorporate hope as a thematic and clinical practice in the training process of these professionals. Keywords: Hope; Mental Health; Mothers; Premature Newborn; Neonatal Intensive Care Units; COVID-19.
Hope and promotion of mental health for mothers of premature infants hospitalized in Neonatal Intensive Care Unit
Keywords: Esperança; Saúde mental; Mães; COVID-19; Recém-nascido prematuro; Unidades de terapia intensiva neonatal; CIENCIAS DA SAUDE::ENFERMAGEM